Argumentasi Fikih Klasik bagi Perempuan Haid dalam Beraktivitas di Masjid, Membaca dan Menyentuh Al-Qur’an - Kudhori, Muhammad (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
When Muslim women had their menstrual cycle or period, they often deal with problems, especially those which related to mosque activities. Because in the mainstream Jurisprudence studied in Islamic boarding schools which is influenced by the Shafi'i madhhab, menstruating women are prohibited from doing activities in the mosque, including holding and reading the Qur’an. This argument will limit their activities in the mosque. Therefore, there have to be some solution to solve this problem. In the classic fiqh discourse, some of ulamas said that they are allowed to do some activities in the mosque, touching/holding and reading the Qur’an. Unfortunately, it is not common for boarding school to use this rule and considered as a weak argumentation, and become rarely applied. Moreover, this argumentation is out of four madhhab. If we research it deeper, this argumentation comes from the credible classic ulamas, which have a strong legal foundation and giving more positive effect for menstruating women. This argumentation can be used as a solution; therefore women can normally do their activities without feeling guilty of breaking the rules, i.e. Islamic rules. In the fiqh and Uṣūl al-Fiqh, even the weakest and uncommon opinion can be applied in the certain times and places based on several reasons.